Recommendations for Preoperative Management of Frailty from the Society for Perioperative Assessment and Quality Improvement (SPAQI) - Alvarez-Nebreda, Maria Loreto; Bentov, Nathalie; Urman, Richard D.; Setia, Sabeena; Huang, Joe Chin-Sun; Pfeifer, Kurt; Bennett, Katherine; Ong, Thuan D.; Richman, Deborah; Gollapudi, Divya; Alec Rooke, G.; Javedan, Houman (Journal of clinical anesthesia, 2018)
Frailty is an age-related, multi-dimensional state of decreased physiologic reserve that results in diminished resiliency and increased vulnerability to stressors. It has proven to be an excellent predictor of unfavorable health outcomes in the older surgical population. There is agreement in recommending that a frailty evaluation should be part of the preoperative assessment in the elderly. However, the consensus is still building with regards to how it should affect perioperative care. The Society for Perioperative Assessment and Quality Improvement (SPAQI) convened experts in the fields of gerontology, anesthesiology and preoperative assessment to outline practical steps for clinicians to assess and address frailty in elderly patients who require elective intermediate or high risk surgery. These recommendations summarize evidence-based principles of measuring and screening for frailty, as well as basic interventions that can help improve patient outcomes. •The perioperative evaluation of elderly patients who require elective major surgery should include a frailty screen.•A positive frailty screen is best followed up with a diagnostic assessment of frailty and when feasible a comprehensive geriatric assessment•Multimodal prehabilitation programs could potentially improve the perioperative prognosis of frail patients.•Preoperative approach for frail older adults should be individualized.•Future studies should test the impact of various frailty interventions on system-centered and on patient-centered outcomes.